Input-to-State Stability in sup norms for hyperbolic systems with boundary disturbances. (July 2021) - Bastin, Georges; Coron, Jean-Michel; Hayat, Amaury
Abstract: We give sufficient conditions for local Input-to-State Stability in C 1 norm of general quasilinear hyperbolic systems with boundary input disturbances. In particular the derivation of explicit Input-to-State Stability conditions is discussed for the special case of 2 × 2 systems.